Dysregulation of NEUROG2 plays a key role in focal cortical dysplasia. Issue 3 (10th March 2018) - Avansini, Simoni H.; Torres, Fábio R.; Vieira, André S.; Dogini, Danyella B.; Rogerio, Fabio; Coan, Ana C.; Morita, Marcia E.; Guerreiro, Marilisa M.; Yasuda, Clarissa L.; Secolin, Rodrigo; Carvalho, Benilton S.; Borges, Murilo G.; et al.
Abstract : Objective: Focal cortical dysplasias (FCDs) are an important cause of drug‐resistant epilepsy. In this work, we aimed to investigate whether abnormal gene regulation, mediated by microRNA, could be involved in FCD type II. Methods: We used total RNA from the brain tissue of 16 patients with FCD type II and 28 controls. MicroRNA expression was initially assessed by microarray. Quantitative polymerase chain reaction, in situ hybridization, luciferase reporter assays, and deep sequencing for genes in the mTOR pathway were performed to validate and further explore our initial study. Results: hsa‐let‐7f ( p  = 0.039), hsa‐miR‐31 ( p  = 0.0078), and hsa‐miR34a ( p  = 0.021) were downregulated in FCD type II, whereas a transcription factor involved in neuronal and glial fate specification, NEUROG2 ( p  < 0.05), was upregulated. We also found that the RND2 gene, a NEUROG2‐ target, is upregulated ( p  < 0.001). In vitro experiments showed that hsa‐miR‐34a downregulates NEUROG2 by binding to its 5′‐untranslated region. Moreover, we observed strong nuclear expression of NEUROG2 in balloon cells and dysmorphic neurons and found that 28.5% of our patients presented brain somatic mutations in genes of the mTOR pathway. Interpretation: Our findings suggest a new molecular mechanism, in which NEUROG2 has a pivotal and central role in the pathogenesis of FCD type II. In this way, we found that the downregulation of hsa‐miR‐34a leads to upregulation of NEUROG2, and consequently to overexpression of the RND2 gene. These findings indicate that a faulty coupling in neuronal differentiation and migration mechanisms may explain the presence of aberrant cells and complete dyslamination in FCD type II. Ann Neurol 2018;83:623–635